Evaluation of Ultrasound-Guided Radiofrequency Ablation as a Treatment Option for Papillary Thyroid Microcarcinoma in the Isthmus: A Retrospective Study - Song, Qing; Gao, Hanjing; Tian, Xiaoqi; Ren, Ling; Lan, Yu; Yan, Lin; Luo, Yukun (Frontiers in Endocrinology, 2021)
Background: About 3% - %-9.2% of papillary thyroid carcinomacarcinomas (PTC) isare found in the isthmus, which has unique anatomic properties, making treatment more challenging. The aim of this study was to evaluate the treatment and undesirable effects of Ultrasound-Guided Radiofrequency Ablationultrasound-guided radiofrequency ablation (RFA) for PTC in the isthmus. Methods: This retrospective case series study assessed 112 patients with single papillary thyroid microcarcinoma in the isthmus, who were pathologically diagnosed before RFA inat the General Hospital of Chinese PLA in 2014-2018. Follow -up was performed by Contrastcontrast-enhanced Ultrasoundultrasound (CEUS) and Ultrasoundultrasound examinations at 1 month, 3 months, , and 6 months and every 6 months thereafter, recording . The complete ablation (CAR), disappearance (DR)), and volume reduction (VRR) rates for of nodules, as well as the incidence of complications, and the rate of lymph-node metastasis. were recorded. Results: The CAR of the tumors was 100%. During follow -up, the volume of coagulation necrosis gradually decreased. DRs at 1, 3, 6, 12, and 18 months after RFA were 0.8% (1/112), 10.7% (12/112), 51.7% (58/112), 91.0% (102/112)), and 100% (112/112), respectively. The VRR evaluated by ultrasound and CEUS gradually increased. One recurrent case (0.8%) was found at 7 months after RFA. No complications, lymph node metastasis confirmed by ultrasound, and abnormal thyroid function were detected.observed. Conclusions: This preliminaryretrospective study showedshows that RFA is effectivebeneficial for the treatment of PTMC in the isthmus.